Identification of blood serum micro‐RNAs associated with idiopathic and LRRK2 Parkinson's disease. Issue 8 (20th March 2014) - Botta‐Orfila, Teresa; Morató, Xavier; Compta, Yaroslau; Lozano, Juan José; Falgàs, Neus; Valldeoriola, Francesc; Pont‐Sunyer, Claustre; Vilas, Dolores; Mengual, Lourdes; Fernández, Manel; Molinuevo, José Luis; Antonell, Anna; et al.
<x xml:space="preserve">Abstract</x> Blood‐cell‐free circulating micro‐RNAs (miRNAs) have been proposed as potential accessible biomarkers for neurodegenerative diseases such as Parkinson's disease (PD). Here we analyzed the serum levels of 377 miRNAs in a discovery set of 10 idiopathic Parkinson's disease (IPD) patients, 10 PD patients carriers of the LRRK2 G2019S mutation (LRRK2 PD), and 10 controls by using real‐time quantitative PCR‐based TaqMan MicroRNA arrays. We detected candidate differentially expressed miRNAs, which were further tested in a first validation set consisting of 20 IPD, 20 LRRK2 PD, and 20 control samples. We found four statistically significant miRNAs that were downregulated in either LRRK2 or IPD (miR‐29a, miR‐29c, miR‐19a, and miR‐19b). Subsequently, we validated these findings in a third set of samples consisting of 65 IPD and 65 controls and confirmed the association of downregulated levels of miR‐29c, miR‐29a, and miR‐19b in IPD. Differentially expressed miRNAs are predicted to target genes belonging to pathways related to ECM–receptor interaction, focal adhesion, MAPK, Wnt, mTOR, adipocytokine, and neuron projection. Results from our exploratory study indicate that downregulated levels of specific circulating serum miRNAs are associated with PD and suggest their potential use as noninvasive biomarkers for PD. Future studies should further confirm the association of these miRNAs with PD. © 2014 Wiley Periodicals, Inc.